Projecting land use changes and its consequences for hydrological response in the New Capital City of Indonesia. Issue 1 (December 2021) - Kurniawan, I; Suhardjono; Bisri, M; Suhartanto, E; Septiangga, B; Munajad, R
Abstract: The Indonesian government intends to build a New Capital City in East Kalimantan Province, with a total development area of 56.000 ha located in existing forest and palm oil plantations. This study will look at the fast changes in land use throughout the urbanization process from 2020 to 2045. They will impact surface runoff and increase flood risk in the future. However, this study primarily focuses on modelling to simulate and predict land use changes in the landscape of the primary river basin in the New Capital City. Land use maps for the years 2013 to 2020 were generated using image classification from Landsat images. The CLUE-S semi-empirical model was used for simulations. The modelling effort included a land use/cover change with three scenarios. The simulation revealed that mainland use/cover types will rapidly increase from 2020 to 2045, particularly in converting forest, fishpond, and plantation areas into urban areas and open fields. According to the New Capital scenario model, the built-up area would continue to expand dramatically with a 742.46 % change. In a future study, a surface runoff will be estimated using the HEC-HMS and SCS-CN models.